A compilation manual of interactive audiovisuals using the flipped classroom method to improve listening skills to fifth grade students at Unidad Educativa particular Sagrados Corazones Salinas, province of Santa Elena, school year 2014-2015. - Benavides Orrala, Claudia (2015)
This proposal is applied to fifth grade students at Unidad Educativa Particular Sagrados Corazones school year 2014-2015. This proposal aims to search solutions to improve the listening skills through the application of extra tools like the use of audiovisuals and flipped classroom method. This is a new way to get better production results in learning and increase their criteria with high reflexive thought because they can use it in their daily classes or at home in order to support their English learning using methodological materials. For this reason the development a manual which contains activities like videos, music, slide and worksheet was made for the teacher or it can be downloaded from you tube, in order to upload in Edmodo platform, where students will do an advance of their classes (Flipped classroom) for improving their learning process. Finally, audiovisuals and flipped classroom are considered a productive help for teachers and students to improve to listening skills.